The Influence of Price, Product Quality and Promotion on Purchase Decisions on the Shopee Marketplace (Case Study on Students of Muhammadiyah University of Sidoarjo) - Mochammad Naufal Achsan; Detak Prapanca (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of Price, Product Quality, and Promotion on Purchase Decisions. This study uses a quantitative approach. Sampling in the study used a accidental sampling technique, with a total of 100 respondents from marketplace Shopee at Muhammadiyah University of Sidoarjo students. Data collection techniques using questionnaires distributed through angket. The data analysis technique in this study used multiple linear regression analysis. Data processing in this study used the SPSS 26 (Statistical Program For the Social Sciences) software program.